Propuesta para el aprovechamiento de residuos orgánicos generados en la plaza de mercado de corabastos para la producción de abono orgánico por compostaje y vermicompostaje (2024)
The project to produce 10 tons of compost per day through composting and vermicomposting is a comprehensive and sustainable initiative that seeks to efficiently manage organic solid waste from the CORABASTOS market and promote more sustainable agricultural practices. Through the combination of these two composting methods, it is intended to recycle and valorize a significant amount of organic matter, converting it into high-quality organic fertilizer, generating environmental, economic and social benefits. The composting process involves the aerobic decomposition of organic materials, such as fruit remains, vegetables, leaves, and other waste of plant and animal origin. The mixture of these materials is subjected to controlled conditions of humidity, temperature and aeration, promoting microbial activity and the decomposition of the materials in a given period of time. This composting method produces an organic fertilizer rich in nutrients and organic matter, which can be used to improve soil fertility and promote the growth of healthy plants.